Comparative Study of Financial Soundness of State and Private Banks in Indonesia - Miladiatur Rahmah; Nora Ria Retnasih (MBIA, 2023)
This study aims to investigate the impact of bank soundness on the return on assets (ROA) experienced by state and private banks over the 2016-2022 fiscal quarters. In this study, a quantitative research method employing secondary data obtained through the official website of the OJK (Financial Services Authority) was used as the research methodology. For this investigation, the panel data regression analysis carried out in EViews 9 was the analytical tool. According to research on state banks, the CAR and LDR variables have only a partially significant effect on ROA. Notwithstanding this, ROA is significantly influenced by the NPL and NIM variables. On the other hand, private banks provide some evidence suggesting that the CAR and NPL variables do not have a significant impact on ROA. Several LDR and NIM variables significantly influence ROA. Keywords: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Non-Performing Loan (NPL), Return On Asset (ROA). Abstrak Tujuan dari penelitian ini adalah untuk mengetahui pengaruh tingkat kesehatan bank terhadap return on asset (ROA) pada bank pemerintah dan swasta periode triwulan 2016-2022. Dalam penelitian ini menggunakan metode penelitian kuantitatif dengan menggunakan data sekunder yang diperoleh melalui situs resmi OJK (Otoritas Jasa Keuangan). Alat analisis yang digunakan dalam penelitian ini adalah analisis regresi data panel menggunakan E-Views 9. Berdasarkan hasil penelitian pada bank pemerintah, secara parsial variabel CAR dan LDR tidak berpengaruh signifikan terhadap ROA. Namun variabel NPL dan NIM berpengaruh secara signifikan terhadap ROA. Di sisi lain, bank swasta menunjukkan bahwa variabel CAR dan NPL tidak berpengaruh signifikan terhadap ROA. Sedangkan variabel LDR dan NIM berpengaruh secara signifikan terhadap ROA. Kata kunci: Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Net Interest Margin (NIM), Non-Performing Loan (NPL), Return On Asset (ROA).